The Road Map of Jindal’s and Tata’s CSR Towards the Upliftment of Handicraft Workers at Ranchi District in Jharkhand State - Ashish Prasad (International Journal of Trends in Humanities, 2024)
The purpose of this research is to look into the Corporate Social Responsibility (CSR) activities undertaken by Tata and Jindal Group to help handicraft artists. Handicrafts are an essential element of India's cultural history and a source of income for many rural populations. However, the industry has several obstacles, including a lack of market access, poor pay, and training opportunities. Two of India's major corporate houses, Jindal and Tata Group, have launched CSR’s projects to assist the growth of handicraft workers. The purpose of this research is to examine the impact of these activities and their efficacy in solving the sector's difficulties. To collect secondary and primary data, CSR coordinators from the Tata and Jindal Groups, and important participants in the handicraft industry. The collection of secondary data will come from a range of sources, including case studies, news articles, and annual reports. The collected data will be analysed using a combination of qualitative approaches, such as content analysis The outcomes of the study will provide insight into Tata and Jindal Group's CSR activities aimed at uplifting handicraft workers. The research will also contribute to the corpus of information concerning CSR and its impact on rural communities. The study's results will assist policymakers, researchers, and practitioners in developing long-term growth plans for the manufacturing industry. Overall, the purpose of this research is to assist handicraft artists in creating a more equitable and sustainable future, while also emphasising the importance of CSR in stimulating the expansion of the handicraft industry.
Keywords: GSDP (Gross State Domestic Product); corporate social responsibility; deficient in demand; economic scenario; recovery in sales; social welfare